Design for Manufacture and Assembly (DFMA) of Chainsaw Housing - Rafai, Noor Hakim; Abdullah, Nur Elleanna Najihah (Research Progress in Mechanical and Manufacturing Engineering, 2023)
This research uses DFMA to analyse 372 XP Husqvarna chainsaws. DFMA is an approach for redesigning a product to reduce costs, manufacturing time, and components. This research aims to apply DFMA analysis and compare actual and redesigned model outcomes. Only 72 of the 322-part model were studied. Through the analysis of DFM, the material and manufacturing method for both remain the same. Manual Design for Analysis (DFA) analysis shows that the present design is 10.44% efficient while the modified model is 11.31% efficient with an improvement of 0.876%. Actual model creation takes 862.15 seconds, whereas redesigned model only took 742.65 seconds. Thus, the new model can be made faster. DFA software was used to analyse assembly time, number of entries, DFA index, and product cost. The new model takes 753.74 seconds and 135 entries. The actual model takes 859.30 seconds, therefore this saves 105.56.  The result for the DFA index 5.8 and 6.6 is for the actual and redesigned models. Overall product costs have fallen 1.26 %, from RM 362.88 to RM 358.32. Comparing manual and software DFA. Manual and software analysis differ by 0.33 % for the existing model and 1.48 % for the modified model with 12.38 % faster.